A new surgical strategy for medically uncontrolled protein-losing enteropathy after Fontan surgery. (16th April 2018) - Cha, Seul Gi; Kim, Gi Beom; Noh, Chung Il; Kim, Woong Han
Abstract: Managing protein-losing enteropathy after Fontan surgery is challenging. We report a case of protein-losing enteropathy associated with Fontan circulation in a 14-year-old boy. He was treated medically for 2 years, without improvement until Fontan takedown and pulsatile bidirectional cavopulmonary shunting were performed.